Destabilization of LiBH4 by SrF2 for reversible hydrogen storage. (8th March 2018) - Zhao, S.X.; Wang, C.Y.; Liu, D.M.; Tan, Q.J.; Li, Y.T.; Si, T.Z.
Abstract: The de-/rehydrogenation features of the 6LiBH4 /SrF2 reactive hydride system have been systematically investigated. It was found that the thermal stability of LiBH4 can be reduced markedly by combining it with SrF2 . Dehydrogenation of the 6LiBH4 /SrF2 system proceeds via the 6LiBH4 + SrF2 → SrB6 + 2LiF + 4LiH + 10H2 reaction, which involves SrH2 as the intermediate product. The dehydrogenation enthalpy change was experimentally determined to be 52 kJ/mol H2 based on the P–C isotherm analysis. For rehydrogenation, LiBH4 and SrF2 were regenerated along with LiSrH3 at 450 °C under ∼8 MPa hydrogen pressure; thus, approximately 5.2 wt% of hydrogen can be released during the second dehydrogenation process. Highlights: Thermal stability of LiBH4 can be reduced markedly by combining it with SrF2 . SrH2 acts as an intermediate product during the dehydrogenation process. Dehydrogenation enthalpy change was experimentally determined to be 52 kJ/mol H2 . 5.2 wt% of hydrogen can be released during the second dehydrogenation process.